Aplikasi Teknologi SMS pada Perhitungan Borang Indikator Kebutuhan Perawatan Ortodonti sebagai Upaya Menyongsong Konsep Ortodonti Masa Mendatang (Future Ortodontic) - Faruk Hoesin (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
Disharmony dentofacial is a condation related to relation between teeth in the same jaw or that with antagonist teeth. The relationship is suspected due to be influenced by the food habits. Food which produces less jaw growth stimulation can influence children tooth development ang leads to the development of crowded teeth based on BPS data, it is reported that 80 million Indonesian children in the growth and development age group, thus it is very important to take in into account their growth and development associated with their jaw and teeth. The indicator of orthodontic treatment need is one of orthodontic instruments has the ability to judge. The treatment threshod for orthodontic treatment in this age group, in future, there are 3 important factors influence orthodontic treatments, (i) awarenes of orthodontic treatment need (ii) Knowledge of the coorectable maloclusion and (iii) patient complience. Those 3 factors can be succesfully achieved it clear information is given to the patients which is supported with digital devices. The use of short message service (SMS) will playan important role in future orthodontic. Its expected that a detail information associated wuth orthodontic treatment will give better acceptance to the patients for orthodontic treatments.